Frank Debenham (1884-1965) - Baird, P.D. (ARCTIC, 1966)
The Polar community has suffered a great loss in the death in November 1965 of Frank Debenham. Debenham was a powerful inspiration to many polar workers, being at the same time a disciplinarian professor of geography and a warm hearted individual who, around his hospitable fireside, could inspire young men to take up a career, or a voluntary immolation into polar exploration. He was definitely the founder of what must be considered the senior Polar Research body of the world, the Scott Polar Research Institute at Cambridge. Many of us have thought out fanciful or practical schemes when confined to tent or igloo in a blizzard. But the idea of a repository of polar information and a centre from which future expeditions could draw their nourishment came to Frank Debenham on the slopes of Mt. Erebus in 1912. At that time he was a member of Capt. Scott's last Antarctic expedition, which ended triumphantly but tragically for the leader and his four companions. Britain and the world were profoundly moved by the death of these brave men and the public subscription to take care of their widows and children exceeded the funds required by a wide margin. It was from this surplus that Debenham's scheme for a Polar Institute was achieved, supported as he was by (Sir) James Wordie and (Sir) Raymond Priestly, two other great Antarctic men. From its inception in 1920-26 until 1946, Debenham was the Director of the Scott Polar Research Institute, and from 1930 Professor of Geography at Cambridge University. Debenham, Griffith Taylor, and Priestly were all three geologists on Scott's last expedition. The first two, Australians by birth, were distinguished founders or chairmen of University Geography Departments; the latter went on to be Vice-Chancellor of two universities and President of the Royal Geographical Society. Scott and Shackleton both knew how to pick men, and Debenham likewise attracted and then stimulated the very best. In these material modern days when a graduate student assistant expects a fat salary, it is of ...